1996
DOI: 10.2337/diab.45.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insulin on Vascular Tone and Sympathetic Nervous System in NIDDM

Abstract: Chronic activation of the sympathetic nervous system may be a pathogenetic mechanism by which hyperinsulinemia induces cardiovascular damage in insulin-resistant NIDDM patients. The influence of physiological hyperinsulinemia (∼ 700 pmol/l) on basal and stimulated sympathetic outflow was studied in 12 lean normotensive subjects with well-controlled NIDDM without complications and in 13 matched control subjects. Forearm blood flow (FBF) was measured with forearm plethysmography; sympathetic nervous system activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 3 publications
5
36
0
2
Order By: Relevance
“…The transcapillary fluid absorption from tissue to blood during control LBNP was of the same magnitude as described earlier (Olsen et al 1999). During HI, LBNP resulted in similar changes in HR, BP and FVR as compared with control LBNP (Tack et al 1996b;Fig. 2).…”
Section: Discussionsupporting
confidence: 61%
“…The transcapillary fluid absorption from tissue to blood during control LBNP was of the same magnitude as described earlier (Olsen et al 1999). During HI, LBNP resulted in similar changes in HR, BP and FVR as compared with control LBNP (Tack et al 1996b;Fig. 2).…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, rats fed a highfructose diet develop insulin resistance accompanied by impaired endothelium-dependent vasodilation [60]. In insulin-resistant people, basal limb blood flow is generally not altered [61,62]. However, insulin's ability to increase total blood flow is significantly impaired in states of insulin resistance.…”
Section: Physiologic Perspectivementioning
confidence: 96%
“…However, animal experiments have indicated that central nervous insulin can induce sympathoexcitation via central nervous autonomous centers as well [35][36][37][38]. Thus, hypertension after insulin administration can be a consequence of a sympathoexcitatory effect in the brain that causes vasoconstriction and remains unopposed by peripheral vasodilatation in insulin-resistant subjects [39][40][41][42]. On this background, the question arises whether the intranasal administration of insulin would likewise affect brain sympathetic nervous centers and consequently increase BP.…”
Section: Introductionmentioning
confidence: 95%